Instruct Green School Culture in Creating Clean and Healthy School at SMP Negeri 1 Taya Kahean - Cici Puspaningrum (STIE Bina Karya, 2026)
This study aims to analyze the role of the principal's leadership in instilling a green school culture as an effort to realize a clean and healthy school at SMP Negeri 1 Raya Kahean. The background of this study is based on the importance of a clean, healthy, and sustainable school environment as an integral part of improving the quality of education and character building of students. This study uses a qualitative approach with a case study method to deeply understand the processes, strategies, and practices of the principal's leadership in building a culture of environmental care. Data collection techniques include in-depth interviews, observations, and documentation studies involving the principal, teachers, students, parents, and other related parties. Data analysis was conducted through interactive stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the principal's leadership plays a strategic role in integrating green school values ​​through policies, role models, and the instilling of clean and healthy living habits. Consistently implemented green school culture has been shown to increase participation by all school members, create a comfortable learning environment, and strengthen the school's image as a clean and healthy school. Thus, green school culture is an important foundation for realizing environmental sustainability and quality education in schools